Antibiotic use in Namibia: prescriber practices for common community infections - Dawn D. Pereko; Martie S. Lubbe; Sabiha Y. Essack (South African Family Practice)
Background: Despite the threat of resistance, the use of antibiotics globally is high and continues to increase. Much of this use is attributed to overprescribing by physicians. The objective of this study was to assess doctors’ management of common community-acquired infections in Namibia.